Teaching and Practicing Listening Skill at the Tertiary Level in Bangladesh: Prospects and Problems - Akter, Roksana (American International Journal of Social Science Research, 2019)
This paper tries to study and investigate on the topic" Teaching and Practicing Listening Skill at the Tertiary Level in Bangladesh: Prospects and Problems". The main objectives of the study is to find out to what extent teachers try to teach listening skill in Bangladesh, to what extent the learners have the scope to practice listening skill in Bangladesh. One hundred undergraduate students took part in this research. Both qualitative and quantitative methods have been used to conduct the study. Two sets of questionnaire have been developed for students as well as teachers to collect data. This paper describes the actual practice of listening skill by the teachers and the students, their behavior and attitudes and the problems they face in practicing Listening skill in Bangladesh. The methodology used for the study was a questionnaire. The results from an analysis of the questionnaire indicate that though most of the universities offer compulsory courses including listening, speaking, reading and writing, learners listening skill is not properly assessed at the tertiary level in Bangladesh. The paper concludes with a few recommendations to enhance the practice of listening skill at the tertiary level in Bangladesh.